Early Thalamic Injury After Resuscitation From Severe Asphyxial Cardiac Arrest in Developing Rats - Ton, Hoai T.; Raffensperger, Katherine; Shoykhet, Michael (Frontiers in Cell and Developmental Biology, 2021)
Children who survive cardiac arrest often develop debilitating sensorimotor and cognitive deficits. In animal models of cardiac arrest, delayed neuronal death in the hippocampal CA1 region has served as a fruitful paradigm for investigating mechanisms of injury and neuroprotection. Cardiac arrest in humans, however, is more prolonged than in most experimental models. Consequently, neurologic deficits in cardiac arrest survivors arise from injury not solely to CA1 but to multiple vulnerable brain structures. Here, we develop a rat model of prolonged pediatric asphyxial cardiac arrest and resuscitation, which better approximates arrest characteristics and injury severity in children. Using this model, we characterize features of microglial activation and neuronal degeneration in the thalamus 24 h after resuscitation from 11 and 12 min long cardiac arrest. In addition, we test the effect of mild hypothermia to 34°C for 8 h after 12.5 min of arrest. Microglial activation and neuronal degeneration are most prominent in the thalamic Reticular Nucleus (nRT). The severity of injury increases with increasing arrest duration, leading to frank loss of nRT neurons at longer arrest times. Hypothermia does not prevent nRT injury. Interestingly, injury occurs selectively in intermediate and posterior nRT segments while sparing the anterior segment. Since all nRT segments consist exclusively of GABA-ergic neurons, we asked if GABA-ergic neurons in general are more susceptible to hypoxic-ischemic injury. Surprisingly, cortical GABA-ergic neurons, like their counterparts in the anterior nRT segment, do not degenerate in this model. Hence, we propose that GABA-ergic identity alone is not sufficient to explain selective vulnerability of intermediate and posterior nRT neurons to hypoxic-ischemic injury after cardiac arrest and resuscitation. Our current findings align the animal model of pediatric cardiac arrest with human data and suggest novel mechanisms of selective vulnerability to hypoxic-ischemic injury among thalamic GABA-ergic neurons.